1997
DOI: 10.1046/j.1365-2249.1997.4671365.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 over-expression in skin is not confined to IgE-mediated skin inflammation

Abstract: SUMMARYIL-13 is produced by T cells and, like IL-4, it can induce the production of IgE and IgG4. In order to investigate if IL-13 is a specific marker for atopic dermatitis (AD), IL-13 gene expression was analysed in chronic lichenified lesions and non-lesional skin of patients with AD, in involved and non-involved skin of patients with psoriasis, in positive tuberculin reactions in non-atopics, and in the skin of healthy control subjects. Patients with AD (n ¼ 9) showed sensitization to common air-borne alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…IL-13 producing T cells, both CD4 + and CD8 + , were significantly reduced in lesional skin as compared to non-lesional psoriatic skin (Figure 4). This is in agreement with a previous study that demonstrated an eightfold decrease in IL-13 mRNA expression in non-lesional versus lesional psoriatic skin (van der Ploeg et al , 1997). Our findings suggest that IL-13 production may play a protective role in non-lesional psoriatic skin by down-regulating pathogenic IL-17 production.…”
Section: Discussionsupporting
confidence: 94%
“…IL-13 producing T cells, both CD4 + and CD8 + , were significantly reduced in lesional skin as compared to non-lesional psoriatic skin (Figure 4). This is in agreement with a previous study that demonstrated an eightfold decrease in IL-13 mRNA expression in non-lesional versus lesional psoriatic skin (van der Ploeg et al , 1997). Our findings suggest that IL-13 production may play a protective role in non-lesional psoriatic skin by down-regulating pathogenic IL-17 production.…”
Section: Discussionsupporting
confidence: 94%
“…Although marked neutrophilia has been reported as a characteristic of both allergen-induced and anti-IgE-induced LPR in humans and dogs 13,15,16,41,52 it is not a typical feature of uninfected AD skin in either species. 11,35,53,54 However, the significance of this response can be difficult to evaluate when 'irrelevant' antigen challenges have not been included in experimental protocols. Our results suggest that the contribution of non-specific inflammatory responses within the LPR may be underestimated if only diluent controls are used.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL‐13 in psoriasis and PsA is yet to be elucidated. IL‐13 and IL‐4 are not detectable in the skin of patients with patients or controls (63,68). However, IL‐13 is increased in the synovial fluid of patients with PsA (69).…”
Section: Th2 Pathwaymentioning
confidence: 99%